SISTEM INFORMASI PELANGGARAN SANTRI ASRAMA AL – KHUZAIMAH PONDOK PESANTREN SALAFIYAH SYAFI’IYAH BERBABIS WEB - Abdus Somad; Wiwik Handayani; Muyessiroh Muyessiroh; Isyqy Najwa Salsabila (CV. Denasya Smart Publisher, 2026)
The development of information technology has provided significant benefits in data management and information dissemination across various sectors, including educational institutions such as Islamic boarding schools. One of the challenges frequently encountered is the manual recording of student violations, which often leads to difficulties in data management, information retrieval, report preparation, and monitoring student discipline. This condition was also found at Al-Khuzaimah Dormitory of Salafiyah Syafi’iyah Islamic Boarding School, where violation records were still maintained using conventional administrative books, resulting in inefficiencies and a higher risk of errors in data processing. This study aims to design and develop a Web-Based Student Violation Information System to assist dormitory administrators in managing student data, violation records, sanctions, and reports in an integrated manner. The research employed a qualitative approach, with data collected through observation, interviews, and documentation studies. The system development process adopted the Waterfall model, which consists of requirements analysis, system design, implementation, integration, and testing stages. The application was developed using PHP as the programming language, MySQL as the database management system, and XAMPP as the local web server. The results indicate that the developed system is capable of facilitating the recording of student violations, managing student information, administering sanctions, and generating reports in a more structured manner. Furthermore, the system improves the speed, accuracy, and security of data management compared to the previous manual approach. Therefore, the implementation of this web-based information system contributes to enhancing administrative efficiency and supports administrators in monitoring and evaluating student discipline more effectively.